Genetic expression changes and pathologic findings associated with hyperhomocysteinemia in human autopsy brain tissue. Issue 1 (8th December 2022) - Weekman, Erica M.; Winder, Zach; Rogers, Colin B.; Abner, Erin L.; Sudduth, Tiffany L.; Patel, Ela; Dugan, Adam J.; Fister, Shuling X.; Wasek, Brandi; Nelson, Peter T.; Jicha, Gregory A.; Bottiglieri, Teodoro; et al.
Abstract: Introduction: Vascular contributions to cognitive impairment and dementia (VCID) are a leading cause of dementia. An underappreciated, modifiable risk factor for VCID is hyperhomocysteinemia (HHcy), defined by elevated levels of plasma homocysteine, most often due to impaired B vitamin absorption in aged persons. Studies aimed at identifying neuropathologic features and gene expression profiles associated with HHcy have been lacking. Methods: A subset of research volunteers from the University of Kentucky Alzheimer's Disease Research Center longitudinal cohort came to autopsy and had ante mortem plasma homocysteine levels available. Brain tissue and blood plasma drawn closest to death were used to measure homocysteine and related metabolites in the current pilot study. Genetic expression profiles of inflammatory markers were evaluated using the Human Neuroinflammation NanoString panel. Further analyses included an evaluation of plasma homocysteine effects on amyloid beta, tau, ionized calcium‐binding adaptor molecule 1, and glial fibrillary acidic protein immunohistochemistry in the frontal and occipital cortices. Analytes and other study outcomes were evaluated in relation to ante mortem HHcy status: We identified 13 persons with normal ante mortem plasma homocysteine levels (<14 µmol/L) and 18 who had high plasma homocysteine levels (≥14 µmol/L). Results: Participants with HHcy demonstrated increased levels of several plasma homocysteine cycle metabolites such as total cysteine, S‐adenosyl‐homocysteine, cystathionine, and choline. Inflammatory gene expression profiles showed a general downregulation in the setting of elevated plasma homocysteine. HHcy was associated with more and longer microglial processes, but smaller and fewer astrocytes, especially in participants of older age at death. HHcy in older participants was also associated with occipital cortex microhemorrhages and increased severity of atherosclerosis throughout the cerebral vasculature. Conclusions: Increased plasma homocysteine and older age were associated with the downregulation of inflammatory gene expression markers in association with significant glial and vascular pathology changes. Impaired immune function is a plausible mechanism by which HHcy increases cerebrovascular damage leading to impaired cognitive function.